Syndicated Lending: Intensification of Transactions and Development of Legal Regulation in Modern Russia - INSHAKOVA, Agnessa O.; GONCHAROV, Alexander I.; KAZACHENOK, Olesya P.; KOCHETKOVA, Svetlana Y. (Journal of Advanced Research in Law and Economics; Vol 8 No 3 (2017): JARLE Volume VIII Issue 3(25) Summer 2017, 2017)
This paper deals with the tendencies of development of the legal regulation of syndicated lending in the modern Russian banking sector. The authors reveal the legal regulation problems, elimination of which will contribute to development of syndicated lending to domestic borrowers and, as consequence, growth of the real sector of the national economy as a whole. The legal nature of a syndicated loan and agreement concluded by the syndicate members is revealed. The authors study the problem of slow development of syndicated lending to economic entities in modern Russia. It is noted that this financial technology has been used abroad for a long time and very successfully, while in the Russian Federation syndicated lending is considered to be an innovative banking product. It is concluded that this situation is due to the absence of the detailed legal regulation of this field of business relations, as well as the poor development of the mutual credit partnership among the commercial banks. However, the institution of syndicated lending enables to transact for the financial support of major innovative projects. The development of this institution will contribute to reducing the risks of the parties involved, as well as intensifying the syndicated lending in Russia.